Ten-year population trends of immunoglobulin use, burden of adult antibody deficiency and feasibility of subcutaneous immunoglobulin (SCIg) replacement in Hong Kong Chinese - Kan, Andy Ka Chun; Leung, Garret Man Kit; Chiang, Valerie; Au, Elaine Yuen Ling; Lau, Chak Sing; Li, Philip Hei (Frontiers in Immunology, 2022)
Background Adult antibody deficiency remains under-recognised and under-studied – especially among Asian populations. Patterns of immunoglobulin use and the feasibility of subcutaneous immunoglobulin (SCIg) replacement among Chinese patients remains unclear. Objective To investigate the trends of immunoglobulin use, burden of adult antibody deficiency and the outcomes of patients on SCIg compared to intravenous immunoglobulin (IVIg) replacement in Hong Kong. Methods Population-wide data of immunoglobulin recipients in Hong Kong between 2012 and 2021, and longitudinal clinical data of adult immunodeficiency patients at Queen Mary Hospital were collected and analysed. Results Total immunoglobulin consumption and recurrent immunoglobulin recipients increased continuously from 175,512g to 298,514g (ρ=0.99, p<0.001) and 886 to 1,508 (ρ=0.89, p=0.001) between 2012-21 in Hong Kong. Among 469 immunoglobulin recipients at Queen Mary Hospital in 2021, 344 (73.3%) were indicated for replacement. Compared to those on IVIg, patients on SCIg replacement had fewer immunodeficiency-related hospitalisations (IRR=0.11, p<0.001) and shorter duration of hospitalisation stay (IRR=0.10, p<0.001) per year, as well as significantly better quality of life (SF-36v2 Health Survey and Life Quality Index). Estimated annual healthcare cost of SCIg replacement per patient was lower than that of IVIg (HKD196,850 [USD25,096] vs HKD222,136 [USD28,319]). Conclusion There was a significantly increasing burden of adult antibody deficiency and immunoglobulin consumption in Hong Kong. SCIg was feasible and more cost-effective when compared to IVIg, with SCIg patients experiencing significantly better clinical outcomes and quality of life.